O Cavalo e a Abertura no discurso das charges da imprensa teresinense (1979-1985) - Gomes, Susy Nathia Ferreira (2016)
The next research proposes a study of the political opening in Brazil, in the period 1979-1985, through analysis cartoons that circulated in major newspapers of Teresina - O Dia e O Estado. This paper seeks to understanding through the illustrations advances and setbacks that occurred during the process, watching the cartoons maintain close relations with the events, and satirize political events and the presidential figure, João Batista Figueiredo. In addition to the illustrations in the research were also appropriate the reports of some cartoonists who drew up the charges in analysis, which served to understand the relationships in the newspaper's premises and understand the production of charge in Teresina.